Formation of Acoustic Interference Based on a Microcontroller for the Suppressor of Unauthorized Speech Recording - Олейніков, А. М.; Білоцерківець, О. Г.; Пулавський, І. М. (MC&FPGA, 2022)
The report analyzes the effectiveness of suppressing unauthorized speech recording with acoustic countermeasures. To significantly increase the efficiency of suppression, it is proposed to adapt the acoustic method taking into account the peculiarities of the propagation of acoustic oscillations in the air and the psychophysical perception of sounds by the human ear. The results of experimental researches are given and the means of counteraction on the basis of the microcontroller are offered.
Keywords: speech; unauthorized recording; microcontroller; speech protection device